We Do Too Many Parathyroidectomies for Calciphylaxis. Issue 4 (15th April 2016) - Nigwekar, Sagar U.; Sprague, Stuart M.
Abstract: Calciphylaxis, a disorder of dermal arteriolar calcification with a distinct predilection for patients with advanced kidney disease, remains an enigmatic condition that challenges clinicians. Observations regarding positive associations between levels of circulating parathyroid hormone (PTH) and the risk of calciphylaxis, combined with experimental data suggesting a pathogenic role of secondary hyperparathyroidism in vascular calcification, have led to the assumption that reducing PTH levels will improve the outcomes in patients with calciphylaxis. This editorial communicates the contemporary data regarding surgical parathyroidectomy as a treatment option for these patients. We raise concerns regarding the quality of available data and discuss the direction of future comparative effectiveness research in this field.